Association of changes in frailty with mortality in the aged with hypertension - Liying Li; Linjia Duan; Bingxue Wang; Kexin Wang; Guodong Niu; Sen He; Jiong Tang (Scientific Reports)
Abstract Previous studies found that frailty has a significant impact on the prognosis of hypertensive patients. However, most of the previous studies only focused on baseline frailty status. The association of changes in frailty with mortality in hypertensive patients is little known. Therefore, we aimed to investigate the association of frailty transitions with all-cause mortality and cardiovascular death in older adults with hypertension. A total of 1827 older hypertensive participants age ≥ 65 years from the Chinese Longitudinal Healthy Longevity Study were included. Frailty status was assessed by a 35-item frailty index (FI). Changes in frailty were evaluated by frailty at baseline (wave 2011) and the second survey (wave 2014), and four types of changes in frailty were identified: remaining non-frail, frail to non-frail, non-frail to frail, and remaining frail. The accelerated failure time model was used to evaluate the association of changes in frailty status with all-cause mortality and cardiovascular death. The dose–response relationship between annual changes in FI and mortality was analyzed using restricted cubic splines (RCS). During 6128.9 person-years of follow-up, a total of 623 all-cause mortality and 131 cardiovascular deaths were recorded. Compared to the remaining non-frail group, the fully adjusted time ratios (TRs) of all-cause mortality were 0.75 (95% CI 0.59–0.96, p = 0.025), 0.48 (95% CI 0.41–0.57, p < 0.001), and 0.45 (95% CI 0.37–0.55, p < 0.001) in the frail to non-frail group, non-frail to frail group, and remaining frail group, respectively. After adjusting for potential confounding variables, the adjusted TRs of cardiovascular death were 0.63 (95% CI 0.36–1.11, p = 0.108), 0.34 (95% CI 0.23–0.48, p < 0.001), and 0.34 (95% CI 0.22–0.53, p < 0.001) in the frail to non-frail group, non-frail to frail group, and remaining frail group, respectively. RCS analysis revealed a non-linear relationship between annual changes in FI and all-cause mortality and cardiovascular death (both p for non-linearity < 0.05). Stratified and sensitivity analysis showed similar results. Frailty is a dynamic process, and worsening in frailty status accelerated all-cause mortality and cardiovascular death in older adults with hypertension. In contrast, improvement in frailty status prolonged the survival time of patients.